2011
DOI: 10.1089/ars.2010.3213
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase 2 Mediates Intermittent Hypoxia-Induced Mitochondrial Complex I Inhibition: Relevance to Blood Pressure Changes in Rats

Abstract: Previous studies identified NADPH oxidases (Nox) and mitochondrial electron transport chain at complex I as major cellular sources of reactive oxygen species (ROS) mediating systemic and cellular responses to intermittent hypoxia (IH). In the present study, we investigated potential interactions between Nox and the mitochondrial complex I and assessed the contribution of mitochondrial ROS in IH-evoked elevation in blood pressure. IH treatment led to stimulus-dependent activation of Nox and inhibition of comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 45 publications
3
76
0
2
Order By: Relevance
“…The decreased Sod2 mRNA was associated with reduced MnSOD activity and elevated ROS levels in the mitochondria. Previous studies have shown that ROS are potent inhibitors of complex I activity (19,20). Indeed, we found reduced activity of complex I, but not complex III, in Hif-2α +/− mice.…”
Section: Breathing (Mean ± Sem) (G-j) Mean (Mbp) Systolic (Sbp) Ansupporting
confidence: 52%
See 1 more Smart Citation
“…The decreased Sod2 mRNA was associated with reduced MnSOD activity and elevated ROS levels in the mitochondria. Previous studies have shown that ROS are potent inhibitors of complex I activity (19,20). Indeed, we found reduced activity of complex I, but not complex III, in Hif-2α +/− mice.…”
Section: Breathing (Mean ± Sem) (G-j) Mean (Mbp) Systolic (Sbp) Ansupporting
confidence: 52%
“…3 E and F), a sensitive biomarker of ROS (18). Mitochondrial electron transport chain (ETC) complex I activity, which is also a target for ROS (19,20), was significantly decreased in Hif-2α +/− mice, whereas ETC complex III activity was unaffected (Fig. 3G).…”
Section: Resultsmentioning
confidence: 97%
“…Outside of the mitochondrion, oxygen can be consumed in the generation of reactive oxygen species and NO by NADPH oxidase and NOS, respectively. 17,18 Because reactive oxygen species and NO have been reported to inhibit mitochondrial function in other systems, 19,20 we investigated whether these processes could also play a role in this situation. Although NAPDH oxidase was functionally expressed in BM-derived DCs 21 ( Figure 2A), specific inhibition of this enzyme complex had no effect on nonmitochondrial oxygen consumption ( Figure 2B), suggesting that this enzyme is not active and does not play a role in impairment of mitochondrial function in these cells.…”
Section: Tlr-driven Impairment Of Mitochondrial Respiration In Dcs Ismentioning
confidence: 99%
“…Such activation leads to hyperpolarization of the plasma membrane, decreased excitability, and lowered metabolic demands (14,223,258). Direct evidence for IH-induced activation of K ATP channels in brain is lacking; however, events leading to neuronal K ATP activation, including ROS production, NO-induced protein kinase G (PKG) signaling, mitochondrial K ATP activation and activation of CaMK (32, 33, 115, 243) were observed to occur in brain following IH exposure (115,243).…”
Section: Central Nervous Systemmentioning
confidence: 99%